2008
DOI: 10.1080/15287390801985562
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Predictors of Short- and Medium Term Outcome in Individuals with Idiopathic Environmental Intolerance (IEI) and Individuals with Somatoform Disorders

Abstract: Idiopathic environmental intolerance (IEI), also known as multiple chemical sensitivity (MCS), is defined as a chronic polysymptomatic condition that cannot be explained by an organic disease. Previous studies suggest that IEI may be a variant of somatoform disorders (SFD), because both disorders overlap with respect to symptoms and psychological features of somatization. However, little is known about the short- and medium-term outcome of IEI and psychological outcome predictors. Two clinical groups (IEI and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 33 publications
(51 reference statements)
2
45
0
2
Order By: Relevance
“…MCS, also known as idiopathic environmental intolerance (IEI), is a syndrome which progresses to multiple organ dysfunction, mainly involving the autonomic nervous system, with extremely low-level chemical exposure [2][3][4][5][6][7][8][9][10]. However, the pathogenesis and underlying mechanisms have not been fully clarified anywhere in the world, and internationally unified diagnostic criteria for MCS have not been established [1].…”
Section: Introductionmentioning
confidence: 99%
“…MCS, also known as idiopathic environmental intolerance (IEI), is a syndrome which progresses to multiple organ dysfunction, mainly involving the autonomic nervous system, with extremely low-level chemical exposure [2][3][4][5][6][7][8][9][10]. However, the pathogenesis and underlying mechanisms have not been fully clarified anywhere in the world, and internationally unified diagnostic criteria for MCS have not been established [1].…”
Section: Introductionmentioning
confidence: 99%
“…26,27 A substantial subset of affected individuals also report multiple food intolerances, [28][29][30] and several studies have demonstrated food triggers in a subset of children with attention-defi cit/hyperactivity disorder (ADHD), migraine, and epilepsy, [31][32][33][34][35][36] as well as adults with schizophrenia. 37,38 Although some investigators label these patients as having somatoform spectrum disorder, 11,39,40 the mean age of onset is typically older than 30 years, 12 a fi nding that is inconsistent with the diagnostic criterion requirement for the earlier age of onset in the Diagnostic and Statistical Manual of Mental Disorders (4th Edition) (DSM-IV) for classic somatization disorder. 41 Apart from etiology, elevated levels of subjective mental distress (eg, somatization, anxiety, depression) are a major factor in increasing health care use across diagnoses in the general population.…”
mentioning
confidence: 99%
“…Ezúton végeredményben a prediszpozíciók (a szorongásra, a szomatizációra és a szomatoszenzoros amplifikációra való fokozott hajlam) megerôsítik a tünetek és a környezeti hatások vélt oksági kapcsolatát (Bailer, Witthöft, & Rist, 2008). Utolsó lépésként ezek az emberek elektromágne-sesen túlérzékenynek címkézik magukat, ami visszahatva, a médiát és a hatóságokat figyelmeztetésekre és óvintézkedésekre sarkallja.…”
Section: Rizikófaktorokunclassified